(untitled) (Global Journal of Human-Social Science, 2012)
The study aims at measuring discrepancy of various boards examination BISE and educational testing and evaluation Agency ETEA in KPK The population of the study consisted of all the Boards of Intermediate Secondary Education in KPK and all the intermediate level students who have appeared in both the above-mentioned examinations The sample of the study was 541 students These students were randomly selected for those who had obtained 60 and above marks in both the examinations during the sessions 2006-07 2007-08 and 2008- 09 The data collected was organized analyzed interpreted and tabulated The study found no significant relationship between the marks scores in board examination and in entry test